Science research writing : for native and non-native speakers of English - Glasman-Deal, Hilary (World Scientific, 2021)
"This book enables STEMM researchers to write effective papers for publication as well as other research-related texts such as a doctoral thesis, technical report, or conference abstract. Science Research Writing uses a reverse-engineering approach to writing developed from extensive work with STEMM researchers at Imperial College London. This approach unpacks current models of STEMM research writing and helps writers to generate the writing tools needed to operate those models effectively in their own field. The reverse-engineering approach also ensures that writers develop future-proof strategies that will evolve alongside the coming changes in research communication platforms. The Second Edition has been extensively revised and updated to represent current practice and focuses on the writing needs of both early-stage doctoral STEMM researchers and experienced professional researchers at the highest level, whether or not they are native speakers of English. The book retains the practical, user-friendly format of the First Edition, and now contains seven units that deal separately with the components of written STEMM research communication: Introduction, Method, Results, Discussion, Conclusion, Abstract and Title, as well as extensive FAQ responses and a new Checklist and Tips section. Each unit analyses extracts from recent published STEMM journal papers to enable researchers to discover not only what to write, but, crucially, how to write it. The global nature of science research requires fast, accurate communication of highly complex information that can be understood by all participants. Like the First Edition, the Second Edition is intended as a clear, do-it-yourself guide to make both the process and the product of STEMM research writing more effective"--